Exploring the Emerging Trends and Issues in Supply Chain Management: A Case of Pakistan - Hussain, Mubashar; Bin Jusoh, Ahmad; Afraz Gillani, Syed (International Journal of Psychosocial Rehabilitation, 2020)
With the increasing speed of globalization and international business expansion, it is evident that the resources in this world are needed to be used in an efficient and effective manner. This highlights the importance of efficient supply chains in developing nations specifically. The particular context of Pakistan will be the focus of this paper discussion. The research used a qualitative thematic analysis to explore the concept of SCM by taking 10 semi-structured interviews with supply chain professionals selected by purposive sampling. Five main themes emerged after the interview analysis, i.e., definition and concept of supply chain management (SCM), issues of SCM, current successful strategies, further successful strategies, and ingredients for further improvement of SCM. This paper offers insights for industry practitioners and organizational managers with a deeper understanding of the dynamics attached with the use and achievement of SCM.